2006
DOI: 10.1110/ps.051899406
|View full text |Cite
|
Sign up to set email alerts
|

Secondary structure, orientation, and oligomerization of phospholemman, a cardiac transmembrane protein

Abstract: Human phospholemman (PLM) is a 72-residue protein, which is expressed at high density in the cardiac plasma membrane and in various other tissues. It forms ion channels selective for K + , Cl ÿ , and taurine in lipid bilayers and colocalizes with the Na + /K + -ATPase and the Na + /Ca 2+ -exchanger, which may suggest a role in the regulation of cell volume. Here we present the first structural data based on synthetic peptides representing the transmembrane domain of PLM. Perfluoro-octaneoate-PAGE of reconstitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 33 publications
8
51
0
Order By: Relevance
“…This suggests that PLM may exist in the membrane as a homooligomer with three or more molecules. This is in agreement with structural data indicating that PLM may exist in the membrane as a tetramer (32). It is thus possible that PLM forms channels, as originally proposed by Moorman et al (40), although the physiological significance of such channels is unclear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that PLM may exist in the membrane as a homooligomer with three or more molecules. This is in agreement with structural data indicating that PLM may exist in the membrane as a tetramer (32). It is thus possible that PLM forms channels, as originally proposed by Moorman et al (40), although the physiological significance of such channels is unclear.…”
Section: Discussionsupporting
confidence: 91%
“…2B). The observed deviation from linearity supports the model that PLM can form homo-oligomers of at least three molecules (32). Effect of PLM Phosphorylation and Ouabain on FRET with NKA-␣1/NKA-␣2-We have shown previously that PLM phosphorylation by PKA and PKC enhances the NKA activity (10,11) and drastically reduces the FRET between canine NKA-␣1 and PLM (9).…”
Section: Interaction Between Plm-yfp and Cfp-nka-␣1/cfp-nka-␣2 As Revsupporting
confidence: 71%
“…The symmetric amide I absorption band centered at ϳ1658 cm Ϫ1 revealed that in all cases, the peptide adopted a predominantly ␣-helical conformation (33), confirming earlier observations (19). The absorption band of the labeled sites centered at 1594 cm…”
Section: Methodssupporting
confidence: 87%
“…3) is a right-handed ␣-helical bundle with a crossing angle close to 0°, whereas local helix tilt angles derived from the IR data vary from 2.5 to 10.1°, depending on the site in question, resulting in an average tilt angle of 7.3°. This is in accordance with previous conventional ATR-FTIR experiments, which indicated an average tilt angle between 0°and 17° (19), if the sample order is not taken into account.…”
supporting
confidence: 93%
See 1 more Smart Citation